2007
DOI: 10.1111/j.1526-4610.2007.00914.x
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of Response to Botulinum Toxin Type A (BoNTA) in Chronic Daily Headache

Abstract: A greater percentage of patients with CM responded to BoNTA than patients with CTTH. Headaches that were predominantly unilateral in location, presence of scalp allodynia, and pericranial muscle tenderness appear to be predictors of response to BoNTA in CM, whereas in CTTH, pericranial muscle tenderness may be a predictor of response.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
88
0
7

Year Published

2009
2009
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 83 publications
(102 citation statements)
references
References 34 publications
7
88
0
7
Order By: Relevance
“…The type of headache is certainly playing a key role; current findings corroborate the effect on chronic migraine rather than on tensiontype headache [10]. The criterion "chronic" proved to be decisive, meaning patients have headaches more than half of the time.…”
Section: Discussionsupporting
confidence: 63%
See 2 more Smart Citations
“…The type of headache is certainly playing a key role; current findings corroborate the effect on chronic migraine rather than on tensiontype headache [10]. The criterion "chronic" proved to be decisive, meaning patients have headaches more than half of the time.…”
Section: Discussionsupporting
confidence: 63%
“…Most of the open studies related positive results, whilst most of the controlled studies reported negative findings [8,10,12,13]. The type of headache is certainly playing a key role; current findings corroborate the effect on chronic migraine rather than on tensiontype headache [10].…”
Section: Discussionsupporting
confidence: 59%
See 1 more Smart Citation
“…Allodynia and scalp tenderness with their chronic daily headache may be a positive indicator for response to BoNTA [3], as may the nature of the pain [4]. Those who have headaches that feel as if there is pressure building from the inside, as if their head was going to explode, are most unlikely to respond to BoNTA, whereas those whose headache pain is more crushing or vice-like or where there is an eye popping sensation have a significantly greater chance for response, whether the headaches be chronic or still episodic in occurrence.…”
Section: Editorial Freitagmentioning
confidence: 99%
“…It decreases the headache frequency, headache intensity, and headache related disability in episodic and chronic migraine patients. In a pilot study [65] to find out the possible predictors of response to botulinum toxin A in the prophylaxis of chronic daily headache. it is seen that chronic migraine patients respond better than chronic tension type of headache, unilateral headache, presence of scalp allodynia, pericranial muscle tenderness appear to be predictors of response to botulinum toxin A in chronic migraine, where as pericranial muscle tenderness may be a predictor of response in chronic type of tension type of headache.…”
Section: Headachementioning
confidence: 99%